Rubberwood processing- Current status and possibilities for improvement - Brion H P (In: Proceedings of the International Forum on Investment Opportunities in the Rubber Wood Industry, 20-22 September 1993, Kuala Lumpur, Malaysia, pp.43-54., 1993)
The current status of the rubberwood processing industries in South and Southeast Asian tropical rubber growing countries is described. Wherever possible, the range of development of major aspects of the industries is described in some detail and areas for possible future improvement are identified. The needs of the industries, together with suggested solutions, are enumerated. Furthermore, sources for technical, administrative and/or financial assistance for the Rubberwood industries' development are also identified.
Keywords: Rubberwood industry; Rubberwood processing